HEAVY METAL CONTAMINATION IN SOIL OF ECONOMIC VEGETABLE PRODUCING AREAS IN PHITSANULOK PROVINCE - Tamdee , Phunnipa; Wachirawongsakorn, Piyada (PSRU Journal of Science and Technology, 2021)
This research was to study the content of heavy metals in the soil for growing five economic vegetables in Bueng Phra Sub-district, Mueang District, Phitsanulok Province, including lettuce, Chinese cabbage, morning glory, Chinese kale, and spring onions for 10 planting plots per each vegetable, and 5 planting plots of parsley with totally 55 planting plots. Heavy metal contents were determined using Atomic Absorption Spectroscopy (AAS). The results found that the soils in vegetable plots were contaminated with averaged lead, copper, zinc, and iron of 2.98±3.06, 10.97±2.48, 32.38±9.52 and 3,898.31±932.89 mg/kg, respectively, while cadmium could not detected in all planting plots. Almost heavy metal contents were within the soil quality standard according to the recommended limits set by Notification of National Environment Board B.E. 2547, excepted iron. However, farmers should change chemical vegetation practice into good agricultural practices (GAP) or organic practice systems will contribute to have good quality produce, sustainable productivity and reduced use of pesticides.